Analyses of Indonesians’ Engagement with the Anticommunist Master Narrative - Haidar Buldan Thontowi; Sofyan Hadi Surya; Yanhizbar Rotanza; Nuhida Kinansa Husainy (Psympathic: Jurnal Ilmiah Psikologi)
Research on narrative engagement centers on personal narratives and how these personal narratives challenge master-narratives. Less attention is paid to narrative engagement in an online context, so the current study aims to explore online narrative engagement of master narratives attached to Indonesia’s 30 September Movement. We observed online political discourse by retrieving 3,057 tweets using the keyword “PKI.” We used content analysis to identify relevant themes. Two main themes emerged and represented either support or opposition toward the anti-communist master-narrative. Most tweets in our dataset supported the anti-communist narrative while the remaining were critical of it. We observed that the tweets found predominantly supported anti-communist narratives. Moreover, our research details the unique mechanisms of narrative engagement operative within the online environment. Additionally, we recommend that reconciliation efforts should adopt a subtle approach in challenging the anti-communist narrative to prevent intense opposition.